Pertumbuhan Ikan Tongkol Lisong (Auxis rochei Risso, 1810) di Perairan Kedonganan, Bali - Ghina Nafis Rahmatullah; Nyoman Dati Pertami; Made Ayu Pratiwi (Current Trends in Aquatic Science, 2022)
Bullet tuna (Auxis rochei) is a type of pelagic fish that has important economic value and is a source of livelihood for fishermen in the waters of Kedonganan, Badung, Bali. This study aims to determine the growth of bullet tuna (Auxis rochei) by analyzing the length frequency distribution, growth patterns, condition factors, age groups, and growth parameters. Sampling of bullet tuna was carried out from January to March 2021, as many as 6 times sampling with a span of once every 14 days. The total samples of bullet tuna obtained were 638 individuals. The distribution of the length distribution of bullet tuna is between 268-376 mm. The results showed that the growth pattern of male and female bullet tuna was negative allometric which indicated that the fish's length increased faster than its weight gain. The condition of bullet tuna in Kedonganan waters based on the results of the study showed that bullet tuna were in a less good condition. The value of the condition factor of the female bullet tuna decreased from January to March, while the condition factor of the male bullet tuna decreased only in February. There was a shift in the age group from observations 1 to 5 in the age group to the right, in contrast to observations from 5 to 6 there was no shift in age groups. The growth coefficient (K) of bullet tuna is 0.57 per year, where the asymptotic length is 387.07 mm and the theoretical age of fish at length 0 is -0.854. Based on the parameters of the growth coefficient, it can be seen that the annual growth of bullet tuna in Kedonganan waters is not fast and not large.